Significantly Increased Risk of All-Cause Mortality Among Type 2 Diabetes Patients Living Alone - Fu, Liyao; Zhou, Ying; Sun, Jiaxing; Xing, Zhenhua; Wang, Yongjun; Tai, Shi (Frontiers in Medicine, 2022)
Background There is a lack of studies evaluating the association between living status and subsequent outcomes in patients with type 2 diabetes (T2DM). Objectives This study aimed to assess the association between living alone and the risk of all-cause mortality in T2DM patients. Methods We performed a secondary analysis in patients with long-lasting T2DM from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study. The primary outcome was all-cause mortality. Multivariable Cox proportional hazard models was used to analyze and compare the hazard ratios (HRs) in patients living alone and with one or more adults. Results This study included 10,249 patients with T2DM. Of these, 2,078 (20.28%) were living alone and 8,171 (79.72%) lived with one or more adults. Over a median total follow-up of 8.8 years, 1,958 patients developed the primary endpoint. The all-cause mortality rates in patients living alone or living with one or more adults were 23.24 and 18.05%, respectively. Cox proportional hazard analysis showed that T2DM patients living alone had significantly higher rate of all-cause mortality than those living with others (HR, 1.34; 95% confidence interval [CI], 1.20–1.48; p < 0.001). After multivariable adjustment, living alone was an independent risk factor for all-cause mortality in patients with T2DM (adjusted HR, 1.27; 95% CI, 1.14–1.41; p < 0.001). Furthermore, the risks of both congestive heart failure (CHF) and fatal coronary heart disease (CHD) among 4,050 propensity score-matched patients were higher for patients living alone (respectively HR, 1.37; 95% CI, 1.08–1.74; p = 0.010; and HR, 1.16; 95% CI, 1.00–1.34; p = 0.047). Conclusions The risk of all-cause mortality was significantly higher in T2DM patients living alone than in those living with one or more adults.